Effect of taping on foot kinematics in persons with chronic ankle instability. Issue 7 (July 2016) - Deschamps, Kevin; Dingenen, Bart; Pans, Femke; Van Bavel, Isabelle; Matricali, Giovanni Arnoldo; Staes, Filip
Abstract: Objectives: To investigate differences in rigid-foot and multi-segmental foot kinematics between healthy (control) and chronic ankle instability (CAI) participants during running and to evaluate the effect of low-Dye (LD) and high-Dye (HD) taping on foot kinematics of CAI subjects. Design: Cross-sectional, comparative study. Methods: Kinematic data of 12 controls and 15 CAI participants were collected by a 3D motion analysis system during running. CAI participants performed barefoot (CAI_BF) running trials as well as trials with taping. A rigid Plug-in gait Model and the Rizzoli 3D Multi-Segment Foot Model were used. Groups were compared using one-dimensional statistical parametric mapping. Results: An increased inversion, a decreased dorsiflexion between the foot and tibia and a decreased external foot progression angle were found during terminal swing and early stance in the CAI_BF group. With respect to the taped conditions, post-hoc SPMt calculations highlighted a more dorsiflexed rearfoot (38–46% running cycle) in the CAI_HD compared to the CAI_LD, and a more inverted Mid-Met angle (6–24% running cycle) in the CAI_LD compared to the CAI_BF condition. Conclusions: This study revealed significant differences in rigid foot and multi-segmental foot kinematics between all groups. As high-dye taping embraces shank-rearfoot and forefoot, it seems to have better therapeutic features with respect to low-dye taping as the latter created a more inverted forefoot which may not be recommended in this population.